Penerapan Zona Selamat Sekolah (ZoSS) terhadap Keselamatan Penyebrang Jalan - Insan Kamal; Sri Wulandari; Aang Gunawan (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2019)
The research objective is to find out and analyze the application of the Safe School Zone (Zoss) to the safety of road crossers. The method used referring to Regulation SK 3236 / AJ / 403 / DRJD / 2006 concerning Tests for the Implementation of Safe School Zones, with normal distribution statistics (Z Test), traffic volume refers to the 1997 Indonesian Road Capacity Manual. The results show that the previous volume traffic and behavior of pedestrian crossing at the School Congratulations Zone (ZoSS) location is not yet safe for 270 Jakarta Junior High School students and the lack of safe School Zone (ZoSS) facilities.